Transitivity in English Textbook: A Discourse Analysis of “Pathway to English Text Book” for SMA/MA Grade X - Jayanti, Widya Mas Mardavam; Farikah, Farikah; Normawati, Afi (Ruang Kata, 2025)
Language plays a central role in the teaching process because they connect, complement knowledge, and shape learners’ worldviews. When learning a language, textbooks play a very important role in conveying language input as well as shaping leaners’ knowledge of language structure and social roles. In Indonesia, English textbooks are expected to meet the Common European Framework of Reference for Languages (CEFR) standards to supports communicative competence across educational level s. However, recent studies show that many high school English textbooks fail to meet the expected ECFR B1 level. Addressing this issue this study investigates how transitivity processes and participants are represented in the reading sections of Pathway to English textbook for SMA/MA Grade X with the aim of discovering how language structures facilitate students’ linguistics and cognitive development. Using descriptive qualitative method and discourse analysis grounded in Halliday’s Systemic Functional Linguistics theorized by Gerot and Wignell, the study analyzes 297 clauses from selected texts. It determines the process types of transitivity and explores participant roles in each process. The results reveal dominance of material processes (51.85%), which implies focus on physical activity and concrete events, followed by elational (29.97%), mental (7.74%), verbal (6.06%), existential (3.03%), and behavioral (1.35%) processes, none of the meteorological processes. Participant roles such as actors and goals mainly took place in material processes, while sensors and phenomena were common in mental processes. This distribution shows that although the textbook offers diversity in types of transitivity, it may fall short in offering balance to ensure diversified linguistic exposure. These findings offer suggestions for textbook developers and teachers to strengthen the expression of the process of transitivity, thus improving English instruction and enriching students’ linguistic and critical thinking skills in EFL context.